Asset Accounting Configuration in SAP ERP A Step-by-Step Guide - Okungbowa, Andrew (Apress : Imprint: Apress, 2016)
In this book, noted expert Andrew Okungbowa explains SAP Asset Accounting (FI-AA) in SAP-ERP, including its associated business benefits, and guides you through the considerable complexities of SAP-ERP configuration. Using FI-AA for fixed asset management enables you to manage assets in multinational companies across a broad range of industries and produce reports to meet various needs in line with legal requirements. Configuring SAP-ERP can be a daunting exercise, however, and there are few resources that address these issues. Asset Accounting Configuration in SAP ERP fills that resource gap by covering the major aspects of SAP FI-AA for anyone with SAP experience and the basic accounting knowledge and bookkeeping skills necessary to apply configuration. It provides configuration explanations in the simplest forms possible and provides step-by-step guidance with illustrations and practical examples. In this book, you'll learn: The details of the FI-AA syllabus How to configure FI-AA accounting in SAP How to integrate FI-AA accounting with other SAP modules How to transfer asset data How to prepare for startup and perform periodic processing.